The use of mindfulness to promote ethical decision making and behavior: Empirical evidence from the public sector in Thailand. (3rd December 2019) - Sutamchai, Kunkanit; Rowlands, Kate E.; Rees, Christopher J.
Summary: The study has two main purposes. First, the study explores core ethical values and behaviors from the perspective of Thai public service organizational leaders. Second, the study investigates the extent to which public sector leaders in Thailand consider Buddhist‐based mindfulness practice to be a potentially effective mechanism for reinforcing core ethical values and behaviors in the public sector in Thailand. Using interview data derived from in‐depth semi‐structured interviews with 12 senior public sector officials in Thailand, the analysis elicits four dimensions of core ethical values and behaviors that are perceived by Thai public service organizational leaders as central to ethical behavior in the public sector. The study also sheds light on the interviewees' positive perceptions towards mindfulness and the role its associated practices can play in promoting ethical decision making and behavior in the public sector in Thailand.